La investigacion en campos de agricultores sobre frijol en dos zonas del Distrito Salamina, Colombia - Ríos G, G. (International Center for Tropical Agriculture, 1987)
The most important characteristics of bean production systems in Aranzazu and Salamina (Caldas, Colombia) are summarized. Information collected in a survey detected the main constraints for bean cultivation in the area such as erosion, diseases, low density population, low-P and acid soils, and drought. A general plan to be developed in the area by the Instituto Colombiano Agropecuario and the Integrated Rural Development project is presented. (CIAT)